2011
DOI: 10.1016/j.jfms.2010.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Azodyl, a synbiotic, fails to alter azotemia in cats with chronic kidney disease when sprinkled onto food

Abstract: The effect of probiotic therapy in chronic kidney disease (CKD) in cats is poorly defined, but gaining in popularity. However, cat owners often prefer to administer probiotics by combining them with food, rather than administering capsules intact, as is prescribed by the manufacturer. The efficacy of such non-recommended administration is unknown. In this double-blinded, controlled clinical trial, 10 cats with naturally-occurring CKD were randomized to receive either a probiotic-prebiotic combination (synbioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Based on prebiotic definition, nondigestible food ingredients such as carbohydrates in the form of soluble fiber can stimulate the growth and/or activity of bacteria. Indeed, in some cases, PSL has been used as prebiotic in different situations [1013]. For instance, in a randomized controlled trial for treatment of patients with ulcerative colitis using synbiotic versus probiotic or prebiotic, PSL has been used as prebiotic and the results have shown that the quality of life in patients has been improved [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on prebiotic definition, nondigestible food ingredients such as carbohydrates in the form of soluble fiber can stimulate the growth and/or activity of bacteria. Indeed, in some cases, PSL has been used as prebiotic in different situations [1013]. For instance, in a randomized controlled trial for treatment of patients with ulcerative colitis using synbiotic versus probiotic or prebiotic, PSL has been used as prebiotic and the results have shown that the quality of life in patients has been improved [10].…”
Section: Resultsmentioning
confidence: 99%
“…Psyllium has been reported as a medicinally active natural polysaccharide for the treatment of constipation, diarrhea, irritable bowel syndrome, inflammatory bowel disease ulcerative colitis, colon cancer, diabetes, and hypercholesterolemia [9]. Moreover, psyllium as a soluble fiber has a potential to stimulate bacterial growth in digestive system, and, in some reports, it has been used as prebiotic [1013]. Prebiotics is defined by Gibson and Roberfroid [14] as “non-digestible food ingredients that beneficially affects the host by selectively stimulating the growth and/or activity of one or a limited number of bacteria in the colon, and thus improves host health.”…”
Section: Introductionmentioning
confidence: 99%
“…The gel structure of psyllium is arabinoxylan, which consist of xylose (backbone) and arabinose (side chains) (Guo et al 2008). The prebiotic effect of psyllium is well known in many cultures, from its consumption to treat and reduce the risk of some gut disorders such as diarrhoea, constipation, chronic kidney disease, ulcerative colitis and irritable bowel syndrome (Rishniw and Wynn 2011). Thus, psyllium can be considered a superior candidate for probiotic encapsulation matrix at both point of its beneficiary effects on the probiotic culture and human gastrointestinal tract health.…”
Section: Introductionmentioning
confidence: 99%
“…8,10,11 Moreover, psyllium as a soluble fiber with the potential to stimulate bacterial growth in digestive system has been used as prebiotic. [12][13][14] Prebiotics are defined as "non-digestible food ingredients that beneficially affects the host by selectively stimulating the growth and/or activity of one or a limited number of bacteria in the colon, and thus improves host health". 15 Considering the health benefits of psyllium in digestive system and its prebiotic activity, we have successfully incorporated psyllium (up to 0.5% w/v) in alginate beads containing probiotic bacteria Lactobacillus acidophilus in our previous work.…”
Section: Introductionmentioning
confidence: 99%